2015
DOI: 10.1088/0964-1726/24/4/045043
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical properties of polyurethane shape memory polymer–experiment and modelling

Abstract: In this paper extensive research on the polyurethane shape memory polymer (PU-SMP) is reported, including its structure analysis, our experimental investigation of its thermomechanical properties and its modelling. The influence of the effects of thermomechanical couplings on the SMP behaviour during tension at room temperature is studied using a fast and sensitive infrared camera. It is shown that the thermomechanical behaviour of the SMP significantly depends on the strain rate: at a higher strain rate highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…Figure shows the variation of the storage modulus ( E’ ) and the loss factor, tan δ , as a function of the temperature for all the synthesized polyurethanes, whereas Table summarizes the glass transition temperatures measured from the maximum in tan δ , T g,DMA . The transition around this temperature was ascribed to the glass transition of the hard segment phase . Therefore, as the hard segment content increases, the corresponding glass transition temperature is higher, which is in agreement with the DSC results.…”
Section: Resultssupporting
confidence: 89%
“…Figure shows the variation of the storage modulus ( E’ ) and the loss factor, tan δ , as a function of the temperature for all the synthesized polyurethanes, whereas Table summarizes the glass transition temperatures measured from the maximum in tan δ , T g,DMA . The transition around this temperature was ascribed to the glass transition of the hard segment phase . Therefore, as the hard segment content increases, the corresponding glass transition temperature is higher, which is in agreement with the DSC results.…”
Section: Resultssupporting
confidence: 89%
“…Pieczyska et al [27] have been studied the thermomechanical properties of polyurethane theoretically and experimentally under different mechanical loadings at temperature of 20°C above and below T g at a strain rate of 2 per second within a strain range of 0.6/s. It was observed that when the temperature been slightly dropped, the thermoelastic effect stepped affected.…”
Section: Thermo-mechanical Behaviormentioning
confidence: 99%
“…True stress-strain curve during loading and unloading of PU-SMP along with thermal images that represented different values of strain[27].…”
mentioning
confidence: 99%
“…In addition to this dominated thermoviscoelastic approach, in recent years, SMP modeling methods have even incorporated molecular dynamic simulation (Diani and Gall, 2007), quantum mechanics (Zhang et al, 2010), multi-scale modeling (Shojaei and Li, 2013), and statistical mechanics (Shojaei and Li, 2014), etc. Of all these methods, the phase evolution approach, first proposed by Liu et al (Liu et al, 2006) and further developed by other researchers (Baghani et al, 2012;Chen and Lagoudas, 2008a, b;Gilormini and Diani, 2012;Guo et al, 2015;Kafka, 2008;Kazakevic̆iūtė-Makovska et al, 2012;Kim et al, 2010;Long et al, 2010;Pieczyska et al, 2015;Qi et al, 2008;Reese et al, 2010;Scalet et al, 2015;Volk et al, 2011;Wang et al, 2009;Xu and Li, 2010) has become another widely used modeling approach due to its ease of application in design.…”
Section: Accepted Manuscriptmentioning
confidence: 99%